PEMBINAAN KOPERASI DI KOTA PEKANBARU - Siti Fatimah; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Cooperative is a form of business activities together with the community that can meet theneeds of economic and social together. Where in accordance with the meaning of theCooperative itself contained in Law no. 17 of 2012 on Cooperatives which states that:Cooperatives are legal entities established by individuals or legal entities cooperatives, withthe separation of the wealth of its members as capital to run the business, which fulfills theshared aspirations and needs in the economic, social and cultural fields in accordance withthe values and principles of the Cooperative. This study aims to determine the Coaching ofCooperative Development by the Department of Cooperatives Small and Medium EnterprisesPekanbaru City and to know the constraints in the Coaching of Cooperative DevelopmentSmall and Medium Enterprises Pekanbaru City. This research uses descriptive qualitativeapproach. Informant research Head of Cooperatives, Head of Sub Division Personnel,General, and Equipment. Data collection techniques by interview, observation, anddocumentation. Data obtained will be analyzed by qualitative descriptive method. Based onthe results of research known that the implementation of co-operative development by theOffice of Cooperative Enterprises, Micro, Small and Medium City Pekanbaru alreadycoaching but not optimal and yet can be said good because the cooperative has a goal toachieve the desired goal to improve the welfare of society as a whole through the institutionalCooperative. There are two factors that become obstacles in the coaching of cooperation bythe Office of Cooperatives Micro Small and Medium Enterprises Pekanbaru city that is internalfactors such as limited facilities and infrastructure, limited funds for coaching program, lackof accurate data of cooperatives, limited human resources (HR) coach cooperative, and fromexternal factors namely: lack of capital Cooperatives, limited human resources, andCooperative business is not run professionally.Keywords: Coaching, Cooperative. Pekanbaru City.